Are Three-Day Voiding Diaries Feasible and Reliable? Results from the Symptoms of Lower Urinary Tract Dysfunction Research Network (LURN) Cohort - Cameron, Anne P. (Neurourol Urodyn, 2019)
AIMS: The aims of this study were to assess completeness of voiding diaries in a research context, and to correlate diary data with patient-reported questionnaires. METHODS: Men and women enrolled in the Symptoms of Lower Urinary Tract Dysfunction Research Network (LURN) were given a 3-day voiding and fluid intake diary to fill-out. Diaries were assessed for completeness and intake-output imbalances. They were assigned to one of four categories based on percentage of missing data and fluid imbalance: no diary submitted, unusable (>40% missing void or intake volumes, or unphysiological fluid imbalance), usable but not complete, and complete. RESULTS: A total of 1,064 participants were enrolled and 85% (n=902) returned the bladder diary. Of the diaries returned, 94% (n=845) had data on 3 separate days, 87% (n=786) had no missing intake volumes, 61% (n=547) had no missing voided volumes, and 70% (n=635) had a fluid imbalance within 3L across the three-day time period, resulting in 50% (n=448) of participants with 100% complete diaries. Younger age was associated with a higher likelihood of not submitting a diary, or submitting an unusable diary. Women had a higher likelihood of submitting an unusable diary, or a usable but incomplete diary. CONCLUSION: Overall, 50% of LURN participants returned voiding diaries with perfectly complete data. Incomplete data for voided volumes was the most common deficiency. There was only moderate correlation between diary data and questionnaire responses, indicating that diaries are a source of unique information.